2019
DOI: 10.1101/2019.12.17.879148
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Near-complete Lokiarchaeota genomes from complex environmental samples using long and short read metagenomic analyses

Abstract: Asgard archaea is a recently proposed superphylum currently comprised of five recognised phyla: Lokiarchaeota, Thorarchaeota, Odinarchaeota, Heimdallarchaeota and Helarchaeota. Members of this group have been identified based on culture-independent approaches with several metagenome-assembled genomes (MAGs) reconstructed to date. However, most of these genomes consist of several relatively small contigs, and, until recently, no complete Asgard archaea genome is yet available. Large scale phylogenetic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The recent success in cultivating the first representative of Lokiarchaeia (“ Candidatus Prometheoarchaeum syntrophicum” MK-D1 [ 14 ]) was a breakthrough in an ongoing discussion about the reliability of metagenome-assembled genomes (MAGs) of Asgardarchaeota ( 15 18 ), as it proved the existence of these enigmatic microbes. “ Ca .…”
Section: Introductionmentioning
confidence: 99%
“…The recent success in cultivating the first representative of Lokiarchaeia (“ Candidatus Prometheoarchaeum syntrophicum” MK-D1 [ 14 ]) was a breakthrough in an ongoing discussion about the reliability of metagenome-assembled genomes (MAGs) of Asgardarchaeota ( 15 18 ), as it proved the existence of these enigmatic microbes. “ Ca .…”
Section: Introductionmentioning
confidence: 99%
“…It was therefore necessary to filter the alignments to ensure only the retention of correctly mapped alignments. We found that filtering long reads with the following criteria (similar to (Caceres et al 2019)) achieved minimal loss of true mapping, while removing almost all of the mismapped reads.…”
Section: Extracting Correctly Mapped Nanopore Readsmentioning
confidence: 96%
“…Furthermore, multiply mapped and chimeric reads required additional filtering to remove. Others have used similar filtering strategies (Caceres et al 2019), but we propose an additional criterion to help reduce the number of chimeric reads. When using the default scoring parameters of minimap2, we propose that a minimum read length of 1000 and a read length to alignment score ratio of less than 0.9 is used for filtering, in addition to percent query coverage of each read.…”
Section: Genome Of Uba1547 Sp002422915mentioning
confidence: 99%
See 1 more Smart Citation
“…All the protocols were carried out in the lab, and the authors were able to achieve up to ∼5.5 M 16S rRNA full-length sequences with exclusive barcode assignments in a single MinION run. Other groups have used MinION devices for characterizing river water [ 45 ], seawater [ 46 ], and marine sediments [ 47 ] through metagenomic sequencing. Even though these experiments were not implemented in the field, they demonstrated the possibility of obtaining higher sequencing yields ( Table 1 ).…”
Section: Portable Sequencing In Natural Environmentsmentioning
confidence: 99%